Dynamic properties of a two-phase boost converter with soft-switching transistors technology - Robert Dixon; Yuriy Dementyev; Genadiy Mikhalchenko; Sergey Gennadievich Mikhalchenko; Sergey Semenov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the work is determined by the need to develop a method for improving the efficiency and reliability of voltage converters reducing the dynamic switching losses of various devices, and decreasing inner energy storage for wide application in consumer electronics and industrial engineering systems. Objective: to provide an alternative way of implementing soft-switching transistors through an inductive energy stored technique of the inductive element for the two-phase boost converter type. The inductive commutation switching element can provide an alternative method, which can improve and raise the technical and economical performance of switched mode power supply (SMPS) devices. Hence, reducing the dynamic losses of the transistors crystalline structure and including the reduction of electromagnetic interference (EMI) occurrences. Methods: reviewing of technical publications concerning hard and soft techniques including their dynamic properties. A modelled simulation of the two-phase boost converter with soft-switching transistors has been studied in variety of software environment, such as SwCAD and MATLAB platform. Thus, the analysis of static and dynamic characteristics of the device incorporates the Newton-Raphson method (e.g. equating vector of state variables real roots in its transient and steady state), which has a sufficiently rapid convergence for a precise value and with a fair degree of accuracy of the discrete values found - shown below in the chaos and bifurcation phenomena regimes. Results: the authors have proposed the voltage converter control system designed on the basis of a two-phase boost converter with soft-switching transistors, which is capable of increasing performance and reliability; hence, the life of the SMPS device. It can also provide high efficiency even at low voltage power supply.